2019
DOI: 10.3390/ijerph16162864
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Undergraduate Students’ Psychological Well-Being as They Experience University Life

Abstract: The onset of most lifetime mental disorders occurs during adolescence, and the years in college, as the final stage of adolescence in a broad sense, deserve attention in this respect. The psychological well-being of undergraduate students can influence not only their academic and professional success, but also the development of society as a whole. Although previous studies suggested psychiatric disorders are common in the adult population, there was little consistent information available about undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 52 publications
10
104
4
5
Order By: Relevance
“…Among Jordanian university students, higher anxiety was reported in females, individuals with the lowest monthly income, those with less coronavirus knowledge, and those who believed the disease was part of a conspiracy [21]. The present results do not differ substantially from previous research conducted before the coronavirus pandemic outbreak [30][31][32][33]. It is confirmed that university and college students experience consistently higher rates of mental health disorders than other populations, which may be slightly elevated by the COVID-19 pandemic and lockdown restrictions.…”
Section: Mental Health In Ukrainian University Studentscontrasting
confidence: 70%
See 1 more Smart Citation
“…Among Jordanian university students, higher anxiety was reported in females, individuals with the lowest monthly income, those with less coronavirus knowledge, and those who believed the disease was part of a conspiracy [21]. The present results do not differ substantially from previous research conducted before the coronavirus pandemic outbreak [30][31][32][33]. It is confirmed that university and college students experience consistently higher rates of mental health disorders than other populations, which may be slightly elevated by the COVID-19 pandemic and lockdown restrictions.…”
Section: Mental Health In Ukrainian University Studentscontrasting
confidence: 70%
“…A review of previous studies conducted before the COVID-19 pandemic showed that depression was present on average in 30.6% of undergraduates [30,31], with significantly higher rates among women. Studies revealed that anxiety has been diagnosed in 12-43% of college and university students [31][32][33]. Thus, there is a need to develop and integrate various prevention and intervention programs at university campuses to cope with stress, anxiety, and depression.…”
Section: Mental Health During the Covid-19 Pandemicmentioning
confidence: 99%
“…7,9,20,21 Social phobia is associated with significant impairment in educational achievement, occupational performance, social interaction, relationships, and quality of life that leads to decrease achievement, lower-income and reduce individuals' quality of life. 9,24 Medical and health science students are often confronted with various stressors and the need to become accustomed suitably to achieve academic and professional success elucidates the importance of having good mental health. 9,25 Therefore, understanding the level of SAD is crucial to reveal facts which can significantly influence a students' mental health and prevent other related problems.…”
Section: Introductionmentioning
confidence: 99%
“…9,24 Medical and health science students are often confronted with various stressors and the need to become accustomed suitably to achieve academic and professional success elucidates the importance of having good mental health. 9,25 Therefore, understanding the level of SAD is crucial to reveal facts which can significantly influence a students' mental health and prevent other related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Answers to such questions are provided by a sociopsychological view of the study load [17], which puts the student and his abilities in the spotlight, where it is true that the individual's success to cope with study conditions is determined by his ability to manage stress. In this context, many universities mention an increase in the prevalence of reported stress, anxiety and depression among university students [18] [19]. For the military university environment, such mental states of students are undesirable not only in connection with the decision to terminate their studies prematurely, but mainly because they could bring significant security risks for the students themselves, as military training involving weapons is conducted during their studies.…”
Section: Theoretical Background Of the Investigated Problemmentioning
confidence: 99%